Macrophage subpopulations and their impact on chronic allograft rejection versus graft acceptance in a mouse heart transplant model - Zhao, Yue (Am J Transplant, 2017)
Macrophages infiltrating the allografts are heterogeneous, consisting of pro-inflammatory (M1 cells) as well as anti-inflammatory and fibrogenic phenotypes (M2 cells); they affect transplant outcomes via diverse mechanisms. Herein, we found that macrophage polarization into M1 and M2 subsets was critically dependent on TRAF6 and mTOR, respectively. In a heart transplant model we showed that macrophage-specific deletion of TRAF6 (LysM(Cre)Traf6(fl/fl)) or mTOR (LysM(Cre)Mtor(fl/fl)) did not affect acute allograft rejection. However, treatment of LysM(Cre)Mtor(fl/fl) recipients with CTLA4-Ig induced long-term allograft survival (>100 days) without histological signs of chronic rejection, whereas the similarly treated LysM(Cre)Traf6(fl/fl) recipients developed severe transplant vasculopathy (chronic rejection). The presentation of chronic rejection in CTLA4-Ig treated LysM(Cre)Traf6(fl/fl) mice was similar to that of CTLA4-Ig treated wild type B6 recipients. Mechanistically, we found that the graft infiltrating macrophages in LysM(Cre)Mtor(fl/fl) recipients expressed high levels of PD-L1, and PD-L1 blockade readily induced rejection of otherwise survival grafts in the LysM(Cre)Mtor(fl/fl) recipients. Our findings demonstrate that targeting mTOR-dependent M2 cells is critical in preventing chronic allograft rejection and that graft survival under such conditions is dependent on the PD-1/PD-L1 co-inhibitory pathway.